The Influence of Intellectual Capital and Personal Growth on Organizational Performance in Micro, Small and Medium Enterprises - Faiz, Deva Nailul; Pratama, Bima Cinintya; Dirgantari, Novi; Hapsari, Ira (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This research aims to test the application of organizational performance to MSMEs in Banyumas, Cilacap, and Brebes Regencies by considering aspects of human capital, structural capital, customer capital, and personal growth. This research used a sample of 200 MSME respondents from the Banyumas, Cilacap, and Brebes Regencies. The sampling was calculated using the Slovin Technique. The population used in this research was 19,044 MSMEs in the Banyumas, Cilacap, and Brebes Regencies. The analytical tool used in this research is Smart-PLS, using an inner model, an outer model, and hypothesis testing. The outer model is used for validity and reliability tests. Inner models were carried out for R-square and F-square tests. Hypothesis testing is carried out through bootstrapping testing. This research shows that the variables human capital, structural capital, customer capital, and personal growth positively affect organizational performance. The implication resulting from this research is that MSME players must optimize their business potential by considering aspects of human capital, structural capital, customer capital, and personal growth to improve organizational performance in MSMEs